Functional Investigation of Plant Growth Promoting Rhizobacterial Communities in Sugarcane - Li, Mingjia; Liu, Ran; Li, Yanjun; Wang, Cunhu; Ma, Wenjing; Zheng, Lei; Zhang, Kefei; Fu, Xing; Li, Xinxin; Su, Yachun; Huang, Guoqiang; Zhong, Yongjia; et al. (Frontiers in Microbiology, 2022)
Plant microbiota are of great importance for host nutrition and health. As a C4 plant species with a high carbon fixation capacity, sugarcane also associates with beneficial microbes, though mechanisms underlying sugarcane root-associated community development remain unclear. Here, we identify microbes that are specifically enriched around sugarcane roots and report results of functional testing of potentially beneficial microbes propagating with sugarcane plants. First, we analyzed recruitment of microbes through analysis of 16S rDNA enrichment in greenhouse cultured sugarcane seedlings growing in field soil. Then, plant-associated microbes were isolated and assayed for beneficial activity, first in greenhouse experiments, followed by field trials for selected microbial strains. The promising beneficial microbe SRB-109, which quickly colonized both roots and shoots of sugarcane plants, significantly promoted sugarcane growth in field trials, nitrogen and potassium acquisition increasing by 35.68 and 28.35%, respectively. Taken together, this report demonstrates successful identification and utilization of beneficial plant-associated microbes in sugarcane production. Further development might facilitate incorporation of such growth-promoting microbial applications in large-scale sugarcane production, which may not only increase yields but also reduce fertilizer costs and runoff.